ЗАБОРОНА ЦЕНЗУРИ В КОНТЕКСТІ ГАРАНТУВАННЯ ПРАВ ЖУРНАЛІСТІВ - Поклонська, Ольга (SUPREMANCE OF LAW, 2017)
The article analyzes the prohibition of censorship as the main element in ensuring freedom of production, dissemination of mass information and guaranteeing effective professional activity of journalists. It is proved that a modern democratic society seeks to ban censorship, freedom of speech and expression, because one of the foundations of a democratic society is free mass information that does not only express universal human values, helps to reveal the potential of the individual, but also is the basis of the spiritual life of society and an instrument for strengthening the identity of the state. Signifi cant attention is paid to the analysis of positive international experience and the adaptation of Ukrainian legislation to issues related to the prohibition of censorship and the legal protection of journalists’ rights.